Penerapan Cognitive Behavior Therapy Untuk Mengurangi Fobia Darah Pada Usia Dewasa Awal Agustini e-mail: - Agustini Agustini (Universitas Mercu Buana Jakarta, 2018)
This research is aimed to the practice of CBT to reduce Blood Phobia in early adults. Blood phobia is an irrational fright that conducted a rejection behavior of blood. CBT itself is the intervention that provide psychoeducation, cognitive restructuration technic, give new skills and deliver some tasks. In this case, cognitive restructuration done to reduce the irrational thinking about their anxiety. While the new skills given such as applied tension can avoid the individual from the unconscious reaction when facing blood stimulus. This research use quasi experimental kind technic with qualitative, and quantitative approach. This is because beside using the interview method, pre-test and pro-test also been involved to measure the anxiety intensity of the participants against the blood before and after the intervention. There are three participants. The result showed that the CBT application that happened during the 9 session can reduce the anxiety towards the blood.